Tarkovsky cinema as poetry - Turovskaya, Maya
This is the first book about Andrey Tarkovsky by a leading Soviet critic to be translated into English. Maya Turovskaya was one of the first to hail Tarkovsky's originality when she saw Ivan's Childhood in 1962. Having followed his career ever since, she has a close familiarity with his sources--especially the poetry of his father Arseniy Tarkovsky--as well as with the archives of Mosfilm Studios.